MENDAMAIKAN KEKRISTENAN DAN LGBT: SEBUAH UPAYA HERMENEUTIK ALKITAB - Emanuel Gerrit Singgih (Institut Filsafat dan Teknologi Kreatif Ledalero, 2020)
This paper challenge to raise the understanding that “the Bible is anti LGBT”. Hermeneutical examination of the six passages or texts shows that in the Bible there are anti-LGBT texts, but there are also pro-LGBT texts. Then the story of Sodom and Gomorrah, often used as “proof” that the Bible is anti-LGBT, can also be interpreted as opposites. Finally there is a hermeneutical discussion about the relationship of religion and science, culture and human rights, and concrete proposals regarding the pastoral actions of the church against LGBT people. Keywords: Hermeneutics, Sola Scriptura Plus, anti-LGBT texts, pro-LGBT texts, religion/theology, science/science, human rights, and restriction.